Keresetek, valorizáció és nyugdíjak: Koncepcionális kérdések és statisztikai problémák - Gábor Obláth; András Simonovits (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2023)
– In Hungary, average initial old age pensions have risen much faster than average pensions over the past decade. Several factors have contributed to this, of which the method of valorization and official earnings statistics are of particular importance. In most countries, initial pensions are determined on the basis of a wage path of several decades, and nominal earnings of each year are valorized (indexed) by the growth of nationwide nominal wages. This is also the method used in Hungary. The comparisons presented in the study show that between 2013 and 2021, the official net wage index may have significantly overestimated the increase in national average net earnings, thus leading to a higher than justified increase in initial pensions. The paper examines several aspects of this issue, including the plausibility of a significant decline in the average pension/net wage ratio, and the dilemmas faced by policymakers in such a situation.
Keywords: H55; 330; pensions; indexation; inconsistency of wage statistics